Workload and work stress with burnout nurses at the Atma Husada Samarinda regional psychiatric hospital during the COVID-19 pandemic - Putri, Anindya Monika; Surono, Agus; Subekti, Heru (BKM Public Health and Community Medicine, 2022)
Purpose: To assess the relationship between work stress and burnout in Atma Husada Samarinda Regional Mental Hospital nurses during the COVID-19 Pandemic. Methods: The research employed an analytical observational method with a cross-sectional study design, utilizing a stratified random sampling technique for data collection. The data obtained will be analyzed using univariate analysis, bivariate analysis with the Chi-Square test and Fisher's exact test, and multivariate analysis with ordinal logistic regression test. The results obtained can be strengthened by the results of observations made during the research. Results: Bivariate analysis revealed no relationship between workload (p = 0.223) and work stress (p = 1.000) and burnout. Tenure (p = 0.018) was a confounding variable related to burnout. Multivariate analysis reveals that heavy work stress is associated with a 97 times greater risk of burnout. Heavy workloads risk 360 times burnout. Conclusion: Nurses with >15 years of service have a higher burnout risk compared to those with ≤15 years. Heavy workload and heavy work stress are at risk of causing burnout in Atma Husada Hospital nurses during the COVID-19 pandemic.